2.5D mass spectrometry imaging of N-glycans in esophageal adenocarcinoma and precursor lesions - Vos, D. R. N.; Meijer, S. L.; Pouw, R. E.; Ellis, S. R.; Heeren, R. M. A.; Balluff, B. (Frontiers in Analytical Science, 2022)
Glycosylation plays an important role in the progression of esophageal adenocarcinoma (EAC). Being able to image these glycosylation changes directly in endoscopic resection specimens could provide useful insights into the molecular mechanisms of the disease progression and potential markers for EAC staging. For this purpose, both 3D and 2.5D matrix-assisted laser/desorption ionization (MALDI) mass spectrometry imaging (MSI) have been employed in this study to investigate glycosidase-cleaved N-glycans in a total of 24 formalin-fixed paraffin-embedded esophageal local excision specimens spanning all stages of disease progression, namely from non-dysplastic Barrett’s esophagus to metastatic EAC. 3D-MSI was first used to estimate the number of sections needed to sufficiently cover the molecular heterogeneity of each stage of progression. This analysis showed that a total of four sections out of 20 were sufficient. This subset of four sections was measured for all remaining specimens and is called 2.5D-MSI. Subsequent analyses of the 2.5D-MSI datasets revealed significant elevations of five high-mannose N-glycans (Man3, Man4, Man6, Man7, and Man8) in EAC and three complex (Hex6HexNAc5, Hex6HexNAc5NeuAc1, Hex7HexNAc6) N-glycans in metastatic EAC as compared to previous stages of the disease. The augmented levels of these glycans in EAC could be explained by publically available gene expression data of enzymes involved in glycosylation. As the role of glycosylation is gaining more interest in MSI and cancer research our results show the added value of combining localized N-glycan levels as provided by MSI with gene expression to gain a deeper understanding of the mechanisms behind N-glycan changes. This gives evidence at multiple levels that specific N-glycosylation plays an important role during progression of dysplasia to EAC and could play a role in patient surveillance.